2014
DOI: 10.1080/10496475.2014.941451
|View full text |Cite
|
Sign up to set email alerts
|

The Effects ofCombretum zeyheriLeaf Extract on Ergosterol Synthesis inCandida albicans

Abstract: The in vitro effects of Combretum zeyheri leaf ethanol extract (CZLE) on ergosterol biosynthesis of Candida albicans were investigated by quantifying the ergosterol in C. albicans in the presence and absence of the extract using UV-visible spectrophotometric analyses. Miconazole was used as the positive control. CZLE showed ergosterol biosynthesis inhibition at sub-inhibitory concentration for growth of C. albicans and also at the MIC (0.08 mg.mL −1 ). The decrease in ergosterol in C. albicans cells was dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The use of Combretum species in folk medicine include treatment of a large range of ailments including headaches, abdominal disorders, fever, gallstones, gastric ulcers, diarrhea, bilharzia, dysentery, hookworm, sore throat, pneumonia, urinary tract cleaning and conjunctivitis. Phytochemical studies on the Combretum genus have demonstrated the presence of various classes of phytoconstituents among them flavonoids, alkaloids, tannins and saponins [ 10 ]. Combretum zeyheri extracts have been shown inhibit ABC-type drug efflux pumps [ 4 ], and inhibit ergosterol synthesis in C. albicans [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Combretum species in folk medicine include treatment of a large range of ailments including headaches, abdominal disorders, fever, gallstones, gastric ulcers, diarrhea, bilharzia, dysentery, hookworm, sore throat, pneumonia, urinary tract cleaning and conjunctivitis. Phytochemical studies on the Combretum genus have demonstrated the presence of various classes of phytoconstituents among them flavonoids, alkaloids, tannins and saponins [ 10 ]. Combretum zeyheri extracts have been shown inhibit ABC-type drug efflux pumps [ 4 ], and inhibit ergosterol synthesis in C. albicans [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies on the Combretum genus have demonstrated the presence of various classes of phytoconstituents among them flavonoids, alkaloids, tannins and saponins [ 10 ]. Combretum zeyheri extracts have been shown inhibit ABC-type drug efflux pumps [ 4 ], and inhibit ergosterol synthesis in C. albicans [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves, stem bark and fruits of both species presented antifungal activity against different Candida spp. (Cock and Van Vuuren, 2015;Fyhrquist et al, 2004;Mangoyi et al, 2015;Masoko et al, 2007;Mutasa et al, 2015;Runyoro et al, 2013). Antiinflammatory activities (inhibition of hematopoietic prostaglandin D2 synthase) were detected in leaves of both species (Chimponda and Mukanganyama, 2015;Eloff et al, 2001;McGaw et al, 2001).…”
Section: Combretaceaementioning
confidence: 99%
“…Meanwhile, the human body has an inherent antioxidative mechanism and many of the biological functions such as the antimutagenic, anti-carcinogenic and anti-aging responses originate from this property (Gocer &Gulcin, 2011 andGulcin, 2012). Medicinal plants also represent a rich source of antimicrobial agents (Mutasa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%